Rahasia Mengajar Ala ESQ dengan Menggunakan Metode SKI (Spiritual, Kreativitas, Dan Intelektual) - Astuti, Juli (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2022)
The purpose of this research is to find out the secrets of ESQ-style teaching using the SKI (spiritual, creative and intellectual) method. ESQ-style teaching is a method used by teachers in the teaching and learning process to shape the tough character of students, increase productivity, and create a happy and inspiring life by using the SKI (Spiritual, Creativity, Intellectual) method which combines three human potentials, namely: Intellectual intelligence (IQ), Emotional (EQ), and Spiritual (SQ). The use of the SKI (spiritual, creativity and intellectual) method can foster learning motivation that comes from within the students themselves spiritually (Why), then the student’s creativity side (How), namely students can look at new ideas to answer problems and problems with intellectually existing theories (What). So that by teaching ESQ style, you can create 4 E Readiness, namely enjoy the show, earn right, energy and enthusiasm, and explain easily. The research method is a literature review or library research (Library Research) in the form of primary sources using a module that is the object of the research, namely the implementation module of the face-to-face training program Training for Teacher and Lecture licensed by Dr. (H.C) Ary Ginanjar Agustian. Using a qualitative approach by describing and outlining the secrets of ESQ-style teaching using the SKI method (spiritual, creative and intellectual). Data collection is carried out by reviewing and exploring several journals, books, and modules as well as other sources of data or information deemed relevant to the study